2017
DOI: 10.1128/jvi.00047-17
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the Dengue Virus Polymerase NS5 and Stem-Loop A

Abstract: The process of RNA replication by dengue virus is still not completely understood despite the significant progress made in the last few years. Stem-loop A (SLA), a part of the viral 5= untranslated region (UTR), is critical for the initiation of dengue virus replication, but quantitative analysis of the interactions between the dengue virus polymerase NS5 and SLA in solution has not been performed. Here, we examine how solution conditions affect the size and shape of SLA and the formation of the NS5-SLA comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 42 publications
1
26
1
Order By: Relevance
“…In contrast to previous studies conducted by Gamarnik and colleagues, our EMSA confirmed the affinity of RdRp with 3′ SL and a sensitive in vitro alpha binding assay provided an apparent K d of ≈3 n m for the interaction between RdRp and SL‐TL . It should be noted that two recent studies in which affinities of DENV RdRp with a 5′‐UTR fragment containing SLA were measured in solution yielded K d values ranging from 53 n m to 142 n m …”
Section: Numerous Genomic Rna Structures Are Involved In Replicationcontrasting
confidence: 63%
“…In contrast to previous studies conducted by Gamarnik and colleagues, our EMSA confirmed the affinity of RdRp with 3′ SL and a sensitive in vitro alpha binding assay provided an apparent K d of ≈3 n m for the interaction between RdRp and SL‐TL . It should be noted that two recent studies in which affinities of DENV RdRp with a 5′‐UTR fragment containing SLA were measured in solution yielded K d values ranging from 53 n m to 142 n m …”
Section: Numerous Genomic Rna Structures Are Involved In Replicationcontrasting
confidence: 63%
“…In these experiments the relative fluorescence change is defined as Δ F obs = F i / F 0 , where F i is the fluorescence intensity at a given titration point and F 0 is the initial value of the fluorescence of the sample. Both F 0 and F i were corrected for background fluorescence at the applied excitation wavelength ( 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…92 The SLA serves as a promoter for viral replication, likely through direct recruitment of the RdRp (NS5). 9395 Downstream of the SLA is a uridine-rich region that acts as a spacer between the two 5′ terminal domains and enhances viral replication. 94 The second domain of the 5′ terminal region extends from the 5′UTR into the C ORF.…”
Section: Biochemistry and Molecular Biology Of Flavivirusesmentioning
confidence: 99%